Selective attention and response set in the Stroop task. - LAMERS, MARTIN J. M.; ROELOFS, ARDI; RABELING-KEUS, INGE M. (Memory & Cognition, 2010)
Response set membership contributes much to the interference in the color-word Stroop task. This may be due to selective allocation of attention to eligible responses or, alternatively, to greater inhibition of distractors that are not responses. In the present article, we report two experiments that were designed to adjudicate between these accounts. In Experiment 1, membership was manipulated on a trial-by-trial basis by cuing the possible responses for each trial. Response time (RT) was longer for distractors that corresponded to a cued, eligible response than to an ineligible one. This cuing effect was independent of the number of different responses. In Experiment 2, the distractor was cued on half the trials. Cuing the distractor decreased RTs on both incongruent and congruent trials. Vincentile analyses in both experiments revealed that the effects were constant throughout the entire RT distributions. These results suggest that response set effects arise because of selective allocation of attention to eligible responses.